Efficacy and safety of metformin for melasma treatment: a systematic review and meta-analysis - Mongkhon, Pajaree; Ruengorn, Chidchanok; Awiphan, Ratanaporn; Phosuya, Chabaphai; Ruanta, Yongyuth; Thavorn, Kednapa; Jamjanya, Sirinda; Chuamanochan, Mati; Nochaiwong, Surapon (Frontiers in Pharmacology, 2023)
Objective: Metformin has recently been demonstrated to have an anti-melanogenic activity. Nevertheless, clinical evidence of the effectiveness of metformin in melasma is lacking. The objective of this study was to assess the efficacy and safety of metformin in the treatment of melasma.Methods: MEDLINE, Embase, PubMed, Cochrane Library (CENTRAL), Scopus, CINAHL, and grey literature databases were searched to 4 October 2022 and updated on 26 February 2023. Randomized controlled trials (RCTs), quasi-RCTs, observational studies, case series, and case reports investigating the efficacy and safety of metformin for melasma were included. The Melasma Area Severity Index (MASI) scores that changed from baseline were pooled using fixed-effects model and expressed as standardized mean differences (SMDs) and 95% confidence intervals (CIs).Results: Three RCTs including 140 patients with melasma were included. The results demonstrated that after eight weeks, 15% topical metformin significantly reduced the MASI score compared to placebo (1 trial; n=60; SMD, -0.56; 95% CI, -1.07 to -0.04; P=0.034). Furthermore, when compared to triple combination cream (TCC), 30% topical metformin demonstrated similar efficacy in reducing the MASI score after eight weeks (2 trials; n=80; SMD, 0.19, 95% CI, -0.25 to 0.63; P=0.390). There was no significant difference between groups in terms of adverse events, except for the burning sensation, which was lower in the 30% topical metformin group (P=0.040).Topical metformin was as effective as TCC in decreasing changes in the MASI score in patients with melasma, with minimum adverse events. Further studies with larger sample sizes, longer follow-up times, and well-designed trials are required.